MENINJAU ULANG TEORI PERTUMBUHAN POPULASI MALTHUSIAN DALAM PERSPEKTIF HAK REPRODUKSI PEREMPUAN DALAM HUKUM KELUARGA ISLAM MENINJAU ULANG TEORI PERTUMBUHAN POPULASI MALHTUSIAN DALAM PERSPEKTIF HAK REPRODUKSI PEREMPUAN DALAM HUKUM KELUARGA ISLAM - Riza Hasan, Syafiq; Jihadul Islam, Fathan; Mu’aziz, Farchan (Al-Majaalis : Jurnal Dirasat Islamiyah, 2024)
This study aims to explore the differences in perspectives between Malthusianism and Islam regarding reproductive issues. The research method employed is a qualitative literature review. The findings reveal that Islam holds a distinct viewpoint from Malthusianism concerning reproduction and population growth. While Malthusianism advocates for reproductive restrictions and population control, Islam encourages having children without limitations, emphasizing the importance of upbringing to raise righteous individuals, as well as efforts to meet their daily needs and recognition of women’s reproductive rights. This perspective is reflected in numerous religious texts urging Muslims to have many offspring. However, Islam does not advocate for increasing the number of children except with careful consideration within the framework of Allah's Sharia. Therefore, the theory proposed by Thomas Robert Malthus is not suitable for implementation by devout Muslims. The significance of this research lies in guiding Muslims to adhere to their religious teachings in managing reproductive issues and population growth.